The 3rd Russia Longitudinal Monitoring Survey of Higher School of Economics User Conference, May 19–20, 2017, Moscow, Higher School of Economics: Conference Report - Kozyreva, Polina; Blagodeteleva, Elizaveta (Journal of Economic Sociology, 2017)
The 3rd Russia Longitudinal Monitoring Survey of Higher School of Economics (RLMS-HSE) User Conference, held May 19–20, 2017, at the National Research University Higher School of Economics with the support of Research Center Demoscope, Institute of Sociology of the Russian Academy of Sciences and University of North Carolina–Chapel Hill, aimed to provide a forum for the discussion of the research projects based on RLMS-HSE. It brought together nearly one hundred scholars from Russia, the United States, the United Kingdom, and the European Union, whose scientific interests spanned various fields of economics, demography, sociology, political sciences, public health, and psychology. The papers, presented at the plenary and parallel sessions, discussed multiple research problems pertaining to labor market and wages, education, retirement, health, ethnicity, migration, and subjective well-being and attitudes. Although an overwhelming majority of the research topics had been recurring themes at the RLMS-HSE events since the inception of the project, the papers did not fail to demonstrate the wealth of opportunities the RLMS-HSE data had to offer. What set this conference apart from previous ones was a pronounced interest in those sections of the RLMS-HSE data that contain detailed information about health. The sessions on this matter included many fruitful discussions concerning objective indicators of health status, a healthy lifestyle, and the use of healthcare services